Cultural diversity: creative city as an urban regeneration tool / Asmma' Che Kasim and Munirah Radin Mohd Mokhtar - Che Kasim, Asmma'; Mohd Mokhtar, Munirah Radin (2021)
The countries with inequities and regional disparities are far from achieving sustainability. Hence, to create a strategy for sustainable urban projection and development, it is important to promote regional and cultural diversity as well as competitiveness. This article examines the concept in a creative city and focuses on conceptual exposition on the social environment and cultural aspects. This preliminary study explores the emergence of creative city's discourses and practices and their significance related to communal identity, sense of place and sense of belongingness. In designing the form of core competency, it will be done in the next phase by determining the regional competence of the industrial development program of the city. The preliminary study shows that the place identity and creativity plays a fundamental role in the change of the image of a city.